Peningkatan Kemampuan Membaca Siswa Menggunakan Metode Speed reading Berbantuan Media Amplop Pintar Kelas IV - Anggraeni, Mira Mediana Ade; Masturi, Masturi; Purwaningrum, Jayanti Putri (WASIS : Jurnal Ilmiah Pendidikan, 2025)
Lowstudent reading skills are influenced by teaching methods that lackvariety and teachers' limitations in selecting interesting reading materials. The purpose ofthis study is to improve teachers' teaching skills, student learning activities, and student reading skills by using the speed reading methodassisted by smart envelope media.This research method used a two-cycle classroom action research (CAR) conducted at Suntri Elementary School, Suntri Village, Gunem District, Rembang Regency, with 10 fourth-grade students as subjects. Data were collected through observation, tests, structured interviews, and documentation, using observation sheets, interview guidelines, and test questions as instruments. Data analysis was conducted descriptively and quantitatively to see the increase in reading ability anddescriptively and qualitatively to describe the activities of teachers and students during theaction.The results of the study showed that teachers' teaching skills improved from 80.5% in cycle I to 90.5% in cycle II. Student activity increased from 72% in cycle I to 92% in cycle II. The results of student reading ability were 70.0% in cycle I and increased to 82.8% in cycle II. Overall, the results of the research conducted over two cycles showed that the speed reading method can improve students' reading skills using smart envelope media in grade IV at SDN Suntri.